The mysterious edge of the heroic world - Konigsburg, E. L. (Atheneum Books for Young Readers, 2007)
Amedeo and William find themselves working together on a house sale for Amedeo's eccentric neighbor, Mrs. Zender, whose house is crammed with memorabilia and stories that date back to Nazi Germany.